2022
DOI: 10.21203/rs.3.rs-2182269/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Therapeutic effect and mechanism of Daikenchuto in a model of methotrexate-induced acute small intestinal mucositis

Abstract: Daikenchuto (DKT) has positive therapeutic effects on improving various gastrointestinal disorders. The present study investigated whether or not DKT has a potential therapeutic effect on chemotherapy-induced acute small intestinal mucositis (CIM) in a rat model. Intraperitoneal injection of 10 mg/kg methotrexate (MTX) every 3 days for a total of 3 doses was used for induction of CIM in a rat model. The MTX and DKT-MTX groups were injected with MTX as above from the first day, and the DKT-MTX and DKT groups we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…3 It was included by the State in the "Catalogue of Ancient Classical Prescriptions (First Batch)" and has been extensively compiled in medical texts throughout the ages. 4 For the treatment of digestive system illnesses such as postoperative ileus (POI), [5][6][7] small intestinal mucositis, 8 chronic constipation, 9 and colitis, 2 DJZD is frequently used as a basic formula and has a long history of clinical application. Modern pharmacological studies have verified that DJZD possesses anti-inflammatory 2 and analgesic, 10 as well as promotes the motor function of the gastrointestinal tract 11 and anti-gastrointestinal tumours.…”
Section: Introductionmentioning
confidence: 99%
“…3 It was included by the State in the "Catalogue of Ancient Classical Prescriptions (First Batch)" and has been extensively compiled in medical texts throughout the ages. 4 For the treatment of digestive system illnesses such as postoperative ileus (POI), [5][6][7] small intestinal mucositis, 8 chronic constipation, 9 and colitis, 2 DJZD is frequently used as a basic formula and has a long history of clinical application. Modern pharmacological studies have verified that DJZD possesses anti-inflammatory 2 and analgesic, 10 as well as promotes the motor function of the gastrointestinal tract 11 and anti-gastrointestinal tumours.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its therapeutic effects, MTX can also therefore exhibit undesirable toxic effects in several tissues, including the liver, kidneys, and intestines (5)(6)(7)(8). Several studies have shown that MTX causes pathologies such as increased oxidative stress in the intestines, apoptosis, epithelial damage, inflammation, and mucositis (7,(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%